Co-design with marginalised people: designers' perceptions of barriers and enablers. Issue 3 (3rd July 2022) - Jagtap, Santosh
ABSTRACT: The base of the world income pyramid, typically known as the Base of the pyramid (BOP), represents low-income people living in developing countries. Co-design with BOP people is crucial for sustained adoption and use of products and services. Based on interviews with practising designers, we identify barriers and enablers that the designers encounter in undertaking various tasks in the process of co-designing with these marginalised people. The findings suggest that a broad range of factors, related to the BOP context, co-design processes and methods, organisational issues, and aspects of collaboration, support or hinder activities in the co-design process. Consideration of these factors, as perceived by the designers, can lead to more impactful co-design with BOP people.